Nutrient Requirement and post Harvest studies on Bush Jasmine (Jasminum sambac Ait) - Nirmalatha JD (Department of Horticulture, College of Agriculture, 2001)
The experiment was conducted at the Department of Horticulture, College of Agriculture, Vellayani during 1998-1999 with the objective to standardise the nutrient requirement in bush jasmine and its post harvest studies. The results of experiment I revealed that the growth characters like length of main shoot, number of primary branches, length of primary and secondary branches, spread of plant in East-West and North-South direction performed well at the highest dose of major nutrients applied viz., 600 kg N, 600 kg P20S and 600 kg K20 ha'. The maximum number of secondary branches was obtained at 450 kg ha! of K20 and P20S' The yield of flowers was highest at lower doses of major nutrients applied viz., 300 kg N, 300 kg P20S and 450 kg K20 ha ". Regarding monthly yield pattern lower levels of nutrients (N and P) gave better yield in general, potassium was effective at 450 kg K20 ha". During the growth period the effect of nutrients applied was significant initially then declined in between and finally the yield increased in tune with the season. The 100 bud weight of flower buds was maximum at 300 kg ha' and 300 kg P20S ha ": The time taken for flower opening delayed at 600 kg P20S ha".